Guardianes del Humedal: Experiencia interactiva digital para conectar a los habitantes del sector de Suba y Engativá con el Humedal Juan Amarillo (2022)
The problem about the proper conservation and care of ecosystems in the city of Bogota, by the inhabitants who live around them has been increasing in recent years and wetlands are no the exception, from this problem is born Guardians of the Wetland, a project that looks to connect the residents of Suba, La Gaitana, with the wetland Juan Amarillo or Tibabuyes wetland, to inform them about the benefits of caring for and conserving the ecosystem, through a purpose of an interactive experience developed in a mobile.